1985
DOI: 10.1002/eji.1830151218
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil activation by lymphokines and T cell clone products in the rat

Abstract: T cell lines and T cell clones derived from inbred Fischer rats and specific for Schistosoma mansoni antigens were established. Cell-free supernatants from the T cell lines demonstrated a marked capacity to enhance IgE- and IgG2a-dependent eosinophil-mediated killing of S. mansoni larvae in vitro. In addition, supernatants from cloned T cells stimulated with concanavalin A or specific antigen, or unstimulated, enhanced IgE-dependent eosinophil-mediated helminthotoxicity. The enhancing activity in both cases wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Veith et al [26] have shown an enhancement of antibody-mediated killing using T cell derived factors, and Auriault et al [6] and Capron et al [27] have described similar ef fects with products derived from mast cells and para sites. Furthermore, our own results with FMLP indi cated that the ADCC response of eosinophils from M.corti infected rats was enhanced, albeit to levels comparable with those of unstimulated eosinophils from animals treated with Sephadex-saline.…”
Section: Discussionmentioning
confidence: 92%
“…Veith et al [26] have shown an enhancement of antibody-mediated killing using T cell derived factors, and Auriault et al [6] and Capron et al [27] have described similar ef fects with products derived from mast cells and para sites. Furthermore, our own results with FMLP indi cated that the ADCC response of eosinophils from M.corti infected rats was enhanced, albeit to levels comparable with those of unstimulated eosinophils from animals treated with Sephadex-saline.…”
Section: Discussionmentioning
confidence: 92%
“…T cell clones (G5 or E23) (1 x 106-4 x lo6 cells/ml) were stimulated for 24 h in the presence of irradiated (2000 rads = 20 Gy) syngeneic APC with or without IPSm (50 pglml; [29]). After washings, T cell clones were maintained for a further 24 h in RPMI containing 5% FCS or in serum-free RPMI.…”
Section: Preparation Of T Cell Clones Supernatants (Sn)mentioning
confidence: 99%
“…The analysis of the various components involved in immunity directed towards Schistosoma mansoni has revealed that its essential features are the participation of antibodies, in cooperation with phagocytic cells or platelets, and thymodependency (6). The analysis of the target antigens present on the schistosomulutn surface, recognized by cytotoxic monoclonal or polyclonal antibodies, has emphasized the preponderant role played by four antigens of 38 (10), 28 (2), 22, and 26 kilodaltons (kDa) (1). Among these molecules, that of 28 kDa is of particular interest since it is present in the in vitro translation products of adult worm RNA (2).…”
mentioning
confidence: 99%